(3GdhGVM aj GdeMGSHI GdYGeI (B:s (3OQhS h JWHjbGJ eMdhdI (B/s - (3Hf QHjY, MfjaIs ((3GdLRGFQ(B: s (3OGQ gheg(B, s, 2008)
(3GdejRGfjI , GdMSGH , JfXje GdYed GdeMGSHj , OQGSI GdUfa GdKGdK GdeNRhfGJ (B: (3YedjGJ GdTQGA h GdHjY , eUGQja Gdfbd , GdJNajVGJ , GdZdGaGJ GdJLGQjI , , OQGSI GdUfa GdKGfj GdGSJKeGQGJ (B: (3GdeMJhi Cge GdMSGHGJ , MjGRI GdGSJKeGQGJ , GdJfGRd Yf GdGSJKeGQGJ , GdMbhb h GdOjhf(B: (3OQGSI HYV GdMSGHGJ , GdChQGb GdJLGQjI , GdQSe Ydi GdbjeI GdeVGaI , GdGehGd GdNUI (B: (3OQGSI Cge GdMSGHGJ , eMGSHI GdYedjGJ Hjf GdhMOGJ , GdGfXeI GdeMGSHI GdCNQi h JUMjM GdGNWGA , GdfXGe GdeQcRj , GdejRGf GdeQHY , ejRGf GdeQGLYI h JUMjM GdGNWGA , eMGSHI GdGLhQ (B: (3GdYfGUQ GdechfI ddCLhQ h CYHGA GdeSJNOe GdCLQjI , GdeYGdLI GdeMGSHjI ddCLhQ , CYeGd fgGjI GdOhQI (B: (3eMJhi CYeGd fgGjI GdOhQI , GdeUGQHa GdGYOGOjI , GdEgJdGcGJ , GdeDhfGJ , MSGHGJ GdfJGFL, GdbhGFe GdTGedI(B.s
(3eQGLY U(B.453s
Keywords: (3GdeMGSHI GdYGeIs; (3GdejRGfjIs; (3JObjb GdMSGHGJs